Angiotensin Converting Enzyme-Inhibitors and Incidence of Non-infectious Uveitis in a Large Healthcare Claims Database. (2nd January 2022) - Sobrin, Lucia; Yu, Yinxi; Li, Ashley; Kempen, John H.; Hubbard, Rebecca A.; VanderBeek, Brian L.
ABSTRACT: Purpose: To determine if angiotensin converting enzyme-inhibitors (ACE-I) alter the incidence of non-infectious uveitis (NIU). Methods: Patients in a large healthcare claims database who initiated ACE-I (n = 695, 557) were compared to patients who initiated angiotensin receptor blockers (ARB, n = 354, 295). A second comparison was also made between patients who initiated ACE-I (n = 505, 958) and those who initiated beta-blockers (BB, n = 538, 109). The primary outcome was incident NIU defined as a first diagnosis code for NIU followed by a second instance of a NIU code within 120 days. For the secondary outcome, a corticosteroid prescription or code for an ocular corticosteroid injection within 120 days of the NIU diagnosis code was used instead of the second NIU diagnosis code. Data were analyzed using Cox regression modeling with inverse probability of treatment weighting (IPTW). Sub-analyses were performed by anatomic subtype. Results: When comparing ACE-I to ARB initiators, the hazard ratio (HR) for incident NIU was not significantly different for the primary outcome [HR = 0.95, 95% Confidence Interval (CI): 0.85–1.07, P = .41] or secondary outcome [HR = 0.96, 95% CI: 0.86–1.07, P = .44]. Similarly, in the ACE-I and BB initiators comparison, the HR for incident NIU was not significantly different comparing ACE-I and BB initiators for either outcome definition or any of the NIU anatomical subtypes. Conclusion: Our results suggest there is no evidence that ACE-I have a protective effect on NIU.